Pengembangan kurikulum dan teori-teori belajar di program studi Pendidikan Agama Islam Universitas Ibn Khaldun Bogor - Bahrum Subagiya (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2022)
The changing times demand the development of the education curriculum. This is because the challenges of life that will be faced are growing. Universities need to adjust the curriculum applied in their respective institutions. This research tries to trace the process of curriculum preparation in one of the study programs of the Faculty of Islamic Studies, namely Islamic Religious Education and how the implementation of the learning process is carried out by each lecturer. This research is a qualitative research with a document and field study approach. The results found that the Islamic Religious Education study program, in designing the curriculum with various approaches, both theological, juridical, philosophical, psychological, and technological. The profile of graduates is clearly illustrated and elaborated by the preparation of a curriculum with a mandatory Semester Credit Unit (SKS) of 135 credits with 57 courses. In practice, the lecturers have used various theories in the learning process, whether nativism, constructivism, behaviorism, empiricism, or convergent with the Islamic values that are in accordance with the ideology of Islamic education which is based on humanism theocentrism.AbstrakPerubahan zaman menuntut pengembangan kurikulum pendidikan. Hal ini dikarenakan tantangan kehidupan yang akan dihadapi semakin berkembang. Karenanya, perguruan tinggi perlu menyesuaikan kurikulum yang diterapkan di lembaganya masing-masing. Penelitian ini mencoba menelusuri proses penyusunan kurikulum di salah program studi Fakultas Agama Islam, yaitu Pendidikan Agama Islam serta bagaimana penerapan proses pembelajaran yang dilakukan oleh setiap dosen. Penelitian ini merupakan penelitian kulitatif dengan pendekatan studi dokumen dan lapangan. Hasil penelitian menemukan bahwa program studi PAI, dalam merancang kurikulum dengan berbagai pendektan, baik teologis, yuridis, filosofis, psikologis, dan teknologis. Profil lulusan tergambar dengan jelas dan dijabarkan dengan penyusunan kurikulum dengan Satuan Kredit Semester (SKS) wajib sebanyak 135 SKS dengan 57 mata kuliah. Dalam praktiknya, para dosen telah menggunakan berbagai teori dalam proses pembelajarannya, baik nativisme, konstruktivisme, behaviorisme, empirisme, ataupun konvergen diwarnai dengan nilai-nilai keislaman yang sesuai dengan ideologi pendidikan Islam yang bercorak humanism theocentrisme.